192 Health Equity Starts with Us: Recommendations from the Indiana Clinical and Translational Sciences Institute Racial Justice and Health Equity Task Force - Sylk Sotto-Santiago; Brownsyne Tucker Edmonds; Sarah Wiehe; Sharon Moe (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: The Indiana CTSI Strategy Committee charged the Racial Justice and Health Equity Taskforce to identify priorities with short-term and long-term goals consistent with the I-CTSI mission. In addition, I-CTSI leadership asked for a general description of current state and the resources necessary to achieve the proposed goals. METHODS/STUDY POPULATION: The Taskforce applied an inclusive excellence model to the way we look at the I-CTSI structure, policies, and programs while performing an environmental scan within and across I-CTSI partner institutions. In order to reach equitable solutions and consensus, listening tours were held with partner stakeholders guided by the SOAR framework for strategic planning. This approach allowed us to assess current resources, needs, and gaps across the system, along with a baseline of measures currently monitored. Taskforce members openly discussed strengths and opportunities for enhancement of current programs and services. In addition, these conversations offered an opportunity to disrupt existing practices and through collective agency we identified priority areas that promote equity, diversity and inclusion. RESULTS/ANTICIPATED RESULTS: The Taskforce identified recurring themes in conversations with all partners, which led to the formation of three working groups that examined recruitment broadly: workforce, staffing, and research participation; professional development across all stakeholders from community members to I-CTSI staff; and data-centered metrics informing current state, decision-making, and accountability. Recommendations included these priorities, content, and implementation strategies. The Taskforce delivered a report to the I-CTSI leadership fostering the promotion of diversity, equity and inclusion along with a systematic collection of gender, race, and ethnicity data for individuals utilizing I-CTSI services and resources requiring additional metrics and tracking. DISCUSSION/SIGNIFICANCE: The pandemic shed light on the manner in which marginalized groups are rendered particularly vulnerable to death and disease by systemic and structural racism. The I-CTSI recognized that we cannot advance population health without attending to root causes of inequity and that includes our internal structure. We offer a potential model for other CTSAs.